Paradoxivena, a new leafhopper genus (Hemiptera: Cicadellidae: Stegelytrinae) from Tibet, China - Wei, Cong; Zhang, Yalin; Webb, M.d. (Zootaxa, 2006)
A new Oriental leafhopper genus, Paradoxivena gen. nov. based on one species, P. zhamuensis sp. nov., from Tibet, China, is described and illustrated, and placed in Stegelytrinae. The relationship between the new genus and other taxa is discussed.